Geotechnical properties of soil for selected sites in Kirkuk city - Mahammed Rashid Abboud; Ahmed Abdel -Hamid al-Obeidi; Manal Samir kader (Tikrit Journal of Pure Science)
The research includes finding geotechnical properties of soil for four different sites in the Kirkuk city is (Al- Fayliq, Al-askary Al-hijaj, Al-moalymeen), physical Tests showed that the soil in most of moisture content sites ( Mc) between (4 -10.5%), while showing the results of specific gravity (Gs) ranging between (2.65-2.73), and the results of grain size analysis of the soils in the study area was observed, (Silt) about (63.28%) Based on the results of atterberg limits has revealed that the type angle of the  soil is, a (ML) in all study areas, while the results of engineering tests showed that the of internal friction values ​​ranged between (27-33)degree and cohesion between (0.32-1.3 kg \ cm2), While the results of the  consolidation in the study area strength ranged are Po (3.38-3.98 kN / m2), Pc (85-110kN / m2), eo (0.397-0.646 %), Cc, (0.148-0.180) Cr,(0 .032-0.036 ), and O.CR the chemical analysis show low gypsum ratio , low organic content and base type with low content of soluble salts the minerals study of the soils using X-ray diffracation in the study areas and showed low clay minerals as well as it contain non- clay minerals such as Quartz calcite  and feldspar